The Importance of Ice Breaking in Public Speaking to Improve Communication Skills - Kamilah, Shafa Tasya; Shoheh, Putri Adiniyah; Suryandari, Meity (International Journal of Education, Information Technology, and Others, 2024)
Ice breaking is type of activity that can be done to change atmosphere in learning process. When teachers can apply it well, the learning atmosphere will be more fun and cheerful, so it helps the teaching-learning process condusive. Ice breaking can be used at the beginning of learning, in the middle of learning and at the end of learning. Through Ice Breaking process, the students will be more understand the material, increase their enthusiasm and motivation, refreshing and refocus their minds. In order to start an effective ice breaking, teacher needs to use their creativity and some facilities as support in classroom. As well as in events, such as seminars and workshops, speaker is a teacher that lead an event, so it requires focus, concentration and responsibility to make sure the audiences understand the material. In this part ice breaking interludes are a necessity to refresh environment and increase audiences' interest of the events. This research uses a descriptive qualitative approach method. It aims to determine the use of Ice Breaking in improving communication skills.